Hubungan Pemberian Asi Eksklusif dan Asi Non Eksklusif Terhadap Kejadian Diare Pada Anak Usia 0-24 Bulan - Syahroni, Siti Zahra Shafira; Souvriyanti, Elsye; Arifandi3, Firman (Publikasi Indonesia, 2022)
The percentage of exclusive breastfeeding in Indonesia is still quite low, which is only 37.3%, followed by 9.3% partial breastfeeding and 3.3% predominant breastfeeding. This is motivated by mothers who give other types of food to babies. Low breastfeeding will affect the incidence of diarrhea in children aged 0-24 months. In Indonesia, the Ministry of Health of the Republic of Indonesia supported by the Indonesian Doctors Association has issued a guideline to reduce diarrhea rates, namely the Five Steps to Complete Diarrhea. A program consists of giving zinc for 10 consecutive days, fluids, selective antibiotics, advice to the patient's family, and breast milk and food. Therefore, it is important to know the relationship between exclusive and non-exclusive breastfeeding on the incidence of diarrhea in children. This study used analytic description with a cross-sectional study design. The population of this study was children aged 0-24 months at YARSI Hospital Jakarta. Data analysis was performed by bivariate analysis. The results showed that of 140 children, 108 people (77.1%) did not have diarrhea and 32 people (22.9%) had diarrhea. There is a significant relationship between exclusive breastfeeding and non-exclusive breastfeeding on the incidence of diarrhea in children aged 0-24 months at YARSI Hospital Jakarta with a p-value of 0.042. As well as the command of Allah SWT to mothers to breastfeed their babies.